2015
DOI: 10.1177/0194599815599381
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Comparing Intranasal Midazolam and Chloral Hydrate for Procedural Sedation in Children

Abstract: Intranasal midazolam and chloral hydrate are both safe and efficacious for pediatric procedural sedation. Chloral hydrate was superior to intranasal midazolam, with an earlier time to onset of sedation, a faster recovery, better satisfaction among parents and the audiologist, and successful sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…The lower efficacy of midazolam in that study may be related to the low dose of 0.2 mg/kg. Stephen et al (21) concluded successful sedation leading to completion of procedure was achieved in 95% of children with chloral hydrate compared with 51% for INM. Probably the differences between individuals, race and age range of the patients led to these differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lower efficacy of midazolam in that study may be related to the low dose of 0.2 mg/kg. Stephen et al (21) concluded successful sedation leading to completion of procedure was achieved in 95% of children with chloral hydrate compared with 51% for INM. Probably the differences between individuals, race and age range of the patients led to these differences.…”
Section: Discussionmentioning
confidence: 99%
“…INM can be rapidly absorbed through the highly vascularized nasal mucosa, resulting in a rapid and reliable onset of action. The shorter half-life, ease of administration, predictability and increased bioavailability by circumventing first-pass metabolism makes it a useful drug in the ED setting (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unreliable, for example Barzegari et al found that this dose resulted in an average onset time of 55 min whilst Majidinejad et al found that only 15% of children given this dose were adequately sedated for CT scanning. Oral chloral hydrate, given in a dose of 50 mg.kg −1 appears to be more reliable ; however, a relatively high proportion of children are liable to spit out the drug.…”
Section: Choice Dose and Mode Of Administration Of Sedative Agentsmentioning
confidence: 99%
“…However, it is unreliable, for example Barzegari et al [12] found that this dose resulted in an average onset time of 55 min whilst Majidinejad et al [13] found that only 15% of children given this dose were adequately sedated for CT scanning. Oral chloral hydrate, given in a dose of 50 mg.kg À1 appears to be more reliable [14]; however, a relatively high proportion of children are liable to spit out the drug.…”
Section: Choice Dose and Mode Of Administration Of Sedative Agentsmentioning
confidence: 99%